Switched Fractional Order Model Reference Adaptive Control for First Order Plants: A Simulation-Based Study - Travieso-Torres, J (American Society of Mechanical Engineers, 2022)
This paper presents the results and analysis of an exhaustive simulation study where switched fractional order model reference adaptive control (SFOMRAC) is used for first order plants, along with the analytical proof of boundedness and convergence of the scheme. The analysis is focused on the controlled system behavior through the integral of the time-weighted squared control error (ITSE) and on the control energy through the integral of the squared control signal (ISI). Controller parameters such as fractional order, adaptive gain, and switching time are varied along the simulation studies, as well as plant parameters and reference models. The results show that SFOMRAC controllers can be found for every plant and reference model used such that both system behavior and control energy can be improved, compared to equivalent nonswitched fractional order and integer order control strategies. Copyright VC 2022 by ASME